2000
DOI: 10.1108/00242530010354074
|View full text |Cite
|
Sign up to set email alerts
|

Academic libraries

Abstract: Reviews current trends in academic, mainly university, libraries. Issues selected for discussion as demonstrating most significant and longer lasting change include lifelong learning, frontline services and their quality, electronic libraries, and coping with continuous change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 2 publications
(2 reference statements)
0
6
0
Order By: Relevance
“…In addition, Friedlander (2002) revealed that about 40% of the users are impeded by insufficient training in how to search for information (p. 5). Thus, this student training/ assistance which teaches them how to access information resources more easily and quickly promotes their effective use of the relevant information technologies, effectively equipping them with the skills needed for life-long learning (Andaleeb & Simmonds, 1998;Branch, 2003;Cader et al, 2006;Charlton, Gittings, Leng, Little, & Neilson, 1999;Gannon-Leary et al, 2006;King, 2002;Morgan & Atkinson, 2000;Ray & Day, 1998). More online databases with high quality provision, off-campus access to Web-based databases (Bao, 2000;Herring, 2001;Kleiner & Hamaker, 1997;Tenopir, 2003) and, in particular, historical and statistical databases would also expand student resources, improve library performance and increase the learning level of the individual.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In addition, Friedlander (2002) revealed that about 40% of the users are impeded by insufficient training in how to search for information (p. 5). Thus, this student training/ assistance which teaches them how to access information resources more easily and quickly promotes their effective use of the relevant information technologies, effectively equipping them with the skills needed for life-long learning (Andaleeb & Simmonds, 1998;Branch, 2003;Cader et al, 2006;Charlton, Gittings, Leng, Little, & Neilson, 1999;Gannon-Leary et al, 2006;King, 2002;Morgan & Atkinson, 2000;Ray & Day, 1998). More online databases with high quality provision, off-campus access to Web-based databases (Bao, 2000;Herring, 2001;Kleiner & Hamaker, 1997;Tenopir, 2003) and, in particular, historical and statistical databases would also expand student resources, improve library performance and increase the learning level of the individual.…”
Section: Discussionmentioning
confidence: 95%
“…Additionally, the provision of guidance and help to students in order to develop searching skills and the knowledge to assess information was also supported by Gannon-Leary et al (2006). Furthermore, Morgan and Atkinson (2000) recognized that libraries, and especially academic libraries, should have staff who are also active researchers so that they are in a position to support students and help them to develop their information searching skills. In addition, Friedlander (2002) revealed that about 40% of the users are impeded by insufficient training in how to search for information (p. 5).…”
Section: Discussionmentioning
confidence: 97%
“…Many universities have restructured their library organisations to try to address the changes that are taking place. It has been estimated that, in the UK, as many as 60 institutions have been converged in some way (Morgan and Atkinson, 2000). As part of this, staffing structures have been altered, sometimes dramatically so, and many librarians have had to take responsibility for services in which they have had little previous experience.…”
Section: Changes In Higher Education and Academic Librariesmentioning
confidence: 99%
“…Garrod (2001) describes the hybrid library as the key change agent in the new higher education environment, where information and communication technology dominates the transferable key skills expected of all UK graduates. This has encouraged a series of challenges to the role and professional standing of all library, computing, professional and para-professional, LIS staff (Morgan and Atkinson, 2000).…”
Section: Review Of the Literature Convergence And The Emergence Of The Hybrid Librarymentioning
confidence: 99%